Understanding the Factors Influencing Nepalese Youth’s Intention to Buy Electric Vehicles - Pandey, Gaurab Raj; Khadka, Bishal Kumar; Khanal, Krishna (Apex Journal of Business and Management, 2025)
Electric vehicles (EVs) are emerging as a sustainable alternative to traditional fossil fuel-powered transportation, offering significant environmental and economic benefits. Despite global advances, EV adoption in developing countries such as Nepal remains limited due to socio-economic and infrastructural challenges. This study investigates the behavioral intentions of Nepalese youth to purchase EVs, focusing on five key factors drawn from the Unified Theory of Acceptance and Use of Technology (UTAUT): performance expectancy, environmental concerns, effort expectancy, social influence, and facilitating conditions. Data was collected through an online survey completed by 289 respondents predominantly from urban areas. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze relationships between these constructs. The results indicate that performance expectancy, environmental concerns, and social influence significantly influence the intention to adopt EVs, while effort expectancy and facilitating conditions did not emerge as significant predictors. These findings highlight the importance of emphasizing practical benefits and environmental impacts of EVs, leveraging social endorsement, and shaping youth-targeted awareness campaigns to accelerate adoption. This research contributes to understanding sustainable transportation adoption in emerging economies, offering valuable insights for policymakers, manufacturers, and marketers aiming to promote EV adoption within Nepal’s youth demographic and support the country’s transition towards a greener, low-carbon transport future